2014
DOI: 10.1111/apps.12040
|View full text |Cite
|
Sign up to set email alerts
|

Brain Biology and Gendered Discourse

Abstract: Despite the greater presence of women in the workforce, their organisational experiences remain different from many men's. Most explanations for this difference are based on cultural socialisation or power and dominance. This paper offers the role of brain biology as a missing mediating link explaining the persistence of gendered communication in organisational discourse. The way men and women talk in interactions is mediated by differences in their brain structure, function, and chemistry. This produces gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 98 publications
(165 reference statements)
0
8
0
Order By: Relevance
“…It is experienced when individuals' plans, desires, and needs are frustrated, and when they perceive the situation as unfair and a threat to their own ego (Arslan, 2010;Slavin-Spenny, Lumley, Thakur, Nevedal, & Hijazi, 2013). The prevailing belief is that women have greater difficulty than do men in expressing their anger, resulting in an increased incidence of anger suppression (Case & Oetama-Paul, 2015). This suppression is believed to result in negative consequences, such as depression, guilt, anxiety, passive aggressiveness, dependency, resentment, lack of selfdefinition, and low self-esteem (Videbeck, 2011).…”
Section: Psychological Biological and Social Differences In Women'smentioning
confidence: 99%
See 3 more Smart Citations
“…It is experienced when individuals' plans, desires, and needs are frustrated, and when they perceive the situation as unfair and a threat to their own ego (Arslan, 2010;Slavin-Spenny, Lumley, Thakur, Nevedal, & Hijazi, 2013). The prevailing belief is that women have greater difficulty than do men in expressing their anger, resulting in an increased incidence of anger suppression (Case & Oetama-Paul, 2015). This suppression is believed to result in negative consequences, such as depression, guilt, anxiety, passive aggressiveness, dependency, resentment, lack of selfdefinition, and low self-esteem (Videbeck, 2011).…”
Section: Psychological Biological and Social Differences In Women'smentioning
confidence: 99%
“…This suppression is believed to result in negative consequences, such as depression, guilt, anxiety, passive aggressiveness, dependency, resentment, lack of selfdefinition, and low self-esteem (Videbeck, 2011). Case and Oetama-Paul (2015) indicated that there are clear sex differences in brain systems, and that sex hormones play a role in reactions to stress and threats. Both men and women have aggressive brain circuits that they use in different ways, thus causing them to become angry at different things.…”
Section: Psychological Biological and Social Differences In Women'smentioning
confidence: 99%
See 2 more Smart Citations
“…The conceptual paper by Case and Oetama‐Paul probed the differences in brain structure, function, and chemistry that explain the contrasting communication styles between men and women. Specifically, the authors developed a biopsychosocial model in which the simultaneous effects of biology, psychology, and socialization are examined for better understanding of the gendered discourse patterns in organizations.…”
mentioning
confidence: 99%